COMPOSITIONAL FEATURES AND AGE OF ALKALINE GRANITES OF THE INGUR MASSIF, WESTERN TRANS-BAIKAL AREA - M. V. Rampilova; M. O. Rampilov; I. A. Izbrodin (Геодинамика и тектонофизика, 2022)
The Ingur alkaline granite massif and the associated Zr-Nb occurrence make up part of the largest Mongolian-Trans-Baikal alkaline granitoid provinces. The massif is composed of arfvedsonite, biotite, and alaskite granites. High content of HREE determines the low La/Ybn (2–7) value and a negative europium anomaly (Eu/Eu*≈0.17). They are depleted in Ba, Sr and enriched in Nb, Ta, Zr, Hf and Y. According to their geochemical properties the rocks of the massif belong to the A-type granites. The rare-metal mineralization of the Ingur granites mainly involves zircon, bastnäsite, monazite, and xenotime. The U-Pb age determined by SHRIMP II with zircon from arfvedsonite granites (272 Ma) indicates the Late Permian formation.